Regionális politika – irányítási modellek - Lackó, László (Tér és Társadalom, 1994)
The study deals with three issues some characteristics of regional conditions aims and functions of the regional policy, interrelations between assertion of regional policy and models of management. As a starting observation it is stated that for the majority of specialists of theoretical and practical fields, the spatial dimension in a socio-economic context does not exist. The spatial conditions of the society mean that the natural, economic, technical etc. phenomena exist in a given spatial distribution, in other words the unevenness is the normai state. Moreover the spatial distributions are changing in time, some of them are changing slowly, others rapidly. Consequently, contradictions appear between regional conditions and the demands of the society. The society applies different tools for the adjustment of regional conditions to the changes. The regional policy is the main tool of the harmonization of regional conditions and social demands. Regional policy should be adopted and declared by an elected body (parliament, local council), as various layers of the society are touched by the regional policy differently, regional planning, as a tool is subordinated to regional policy. The chances of realization of regional policies depend on the form of the state (unitarian-federal, autocratic-democratic), sensitivity to inequalities, the attitude to market or state paternalistic orientation, availability of resources, specialized funds, involvement and strength of non-governmental organizations chambers, etc. In principle better chances are offered by unitarian, autocratic, reach and homogeneous state.